Aktivitas antioksidan ekstrak air daun kelor (Moringa oleifera) dengan metode DPPH serta analisis kualitatif kandungan metabolit sekunder - Laili Muna (Sasambo Journal of Pharmacy, 2022)
Sunlight contains UV radiation which will have an impact on the skin if exposed continuously and cause premature aging of the skin. The use of cosmetic products that contain antioxidant compounds is needed to avoid premature aging due to exposure to UV rays. Antioxidants used in cosmetics generally come from synthetic compounds, namely BHT (Butyl hydroxytoluene) whose use will have a negative impact on the skin if used in the long term, so in this study, Moringa oleifera leaf was used as a natural antioxidant. The purpose of this study is to determine the antioxidant activity of Moringa leaf water extract by calculating IC50 and using a comparison standard of vitamin C. The method used in this study is the stratified maceration method with measurement of antioxidant activity using the DPPH method. The results showed that the aqueous extract of Moringa leaves contains secondary metabolites of flavonoids, tannins, saponins, and alkaloids that play a role in antioxidant activity. The test results of Moringa leaf water extract showed moderate antioxidant activity with an IC50 value of 87.54 ppm, while the comparison control vitamin C obtained an IC50 of 483.53 ppm. This is because vitamin C has been oxidized so that the ability to donate protons to DPPH free radicals is also reduced.